Crystal structure of (E)-2-({4-hydroxy-5-methoxy-3-[(4-methyl-1-piperazinyl)methyl]phenyl} methylidene)-1-indanone, C23H26N2O3 - Akkurt, Mehmet; Gül, Halise İnci; Tuğrak, Mehtap; Şahi̇n, Ertan; Aydin, Abdullah (Walter de Gruyter GmbH, 2016)
Abstract C23H26N2O3, triclinic, P1̅ (No. 2), a = 10.6646(19) Å, b = 10.7784(17) Å, c = 11.150(2) Å, α = 67.787(7)°, β = 64.309(7)°, γ = 64.271(7)°, V = 1011.6(3) Å3, Z = 2, R gt(F) = 0.0502, wR ref(F 2) = 0.1481, T = 293 K.
Keywords: Crystallography; QD901-999; Physics; QC1-999